Forecast of the development of the electric vehicle market in the republic of Kazakhstan until 2030 - Tokmurzina-Kobernyak, Natalya; Mussabekova, Aisha; Kisselyova, Olga; Aikumbekov, Muslim; Abdullayev, Seidulla (International Journal of Innovative Research and Scientific Studies, 2025)
The article presents a comprehensive analysis of the current trends and future prospects for the development of the electric vehicle (EV) market in the Republic of Kazakhstan through 2030. The study integrates an examination of the regulatory environment, the existing charging infrastructure, as well as the identification of key barriers and enabling factors influencing market growth. Utilizing a combination of forecasting methodologies—including logistic growth models, the Bass diffusion model, exponential smoothing techniques, and polynomial regression—the research provides scenario-based projections of the EV fleet size. Results indicate a potential expansion ranging from 37,000 to 120,000 electric vehicles by 2030, depending on the intensity of policy support and market dynamics. The analysis highlights critical success factors necessary for the effective implementation of both governmental policies and private sector initiatives aimed at promoting low-carbon transportation. These findings offer valuable insights for policymakers, industry stakeholders, and researchers engaged in the sustainable development of Kazakhstan’s automotive sector, emphasizing the importance of coordinated efforts to overcome infrastructural and regulatory challenges in fostering the widespread adoption of electric vehicles.